Perancangan Sistem Informasi Pembuatan Konten Media Sosial PT. Bikin Kreatif Digital Agency Purwokerto - Joko Dwi Mulyanto; Sutrisno Sutrisno; Brigita Adha Safira; Supriatiningsih Supriatiningsih (Informatics and Computer Engineering Journal, 2023)
Abstracts - Technological developments are progressing rapidly. Systems continue to emerge with various new innovations that are needed by the wider community. Many agencies and companies are competing to digitize their systems. The availability of sufficient information systems can support fast and simple performance so as to achieve efficiency. One of them is developing in the world of marketing, from a conventional system to a modern one. This change follows sophisticated applications that continue to appear, one of which is Instagram. Content on Instagram is now a marketing place that can reach all circles. The purpose of this research is to design a social media content creation system that can be used to facilitate the work of staff every day and facilitate monitoring of staff work and the achievements of projects being worked on. Methods of observation, interviews and literature study were used to obtain the necessary data. By using a web information system, recording client data, processing content ideas and captions, and managing designs more organized and easily accessible and with a web information system, it is easier for staff at PT. Make Creative Digital Agency (Social Media Admin, Content Writer and Graphic Designer) at work.